Entangled photons from subwavelength nonlinear films - Santiago-Cruz, Tomas; Sultanov, Vitaliy; Zhang, Haizhong; Krivitsky, Leonid A.; Chekhova, Maria (Optics Letters, 2021)
Miniaturized entangled photon sources, in particular based on subwavelength metasurfaces, are highly demanded for the development of integrated quantum photonics. Here, as a first step towards the development of quantum optical metasurfaces (QOMs), we demonstrate generation of entangled photons via spontaneous parametric down-conversion (SPDC) from subwavelength films. We achieve photon pair generation with a high coincidence-to-accidental ratio in lithium niobate and gallium phosphide nanofilms. By implementing the fiber spectroscopy of SPDC in nanofilms, we measure a spectrum with a bandwidth of 500 nm, limited only by the overall detection efficiency. The spectrum reveals vacuum field enhancement due to a Fabry-Perot resonance inside the nonlinear films. It also suggests a strategy for observing SPDC from QOM. Our experiments lay the groundwork for future development of flat SPDC sources, including QOM. (C) 2021 Optical Society of America
CRIS-Team WoS Importer:2021-03-19